Tyāgarāju ātmavivicāraṃ - Kāmēśvararāvu, Bhamiḍipāṭi, 1897-1958 (SAMP early 20th-century Indian books project, 1949)
On the life and works of Tyāgarāja Swami, 1767-1847, music composer in Karnatic style.